1974
DOI: 10.1128/aac.6.6.672
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-Resistant Mechanisms in Pseudomonas aeruginosa : Effects of Penicillin G and Carbenicillin on Transpeptidase and d -Alanine Carboxypeptidase Activities

Abstract: A membrane fraction from Pseudomonas aeruginosa KM 338 was shown to catalyze in vitro peptidoglycan synthesis from uridine 5'-diphosphate-N-acetylmuramyl-L-alanyl-D-glutamyl-meso-diaminopimelyl-D-alanyl-D-alanine and uridine 5'-diphosphate-N-acetylglucosamine. Synthesized peptidoglycan was partially cross-linked by transpeptidation, which was accompanied by the release of D-alanine. This reaction was strongly inhibited by 25 and 50 ,ug of penicillin G and carbenicillin per ml respectively, whereas the intact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
15
0

Year Published

1975
1975
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
(14 reference statements)
2
15
0
Order By: Relevance
“…In a previous paper (27) it was reported that the membrane fraction derived from P. aeruginosa KM 338 catalyzes peptidoglycan synthesis, including the cross-linking reaction. This transpeptidase is inhibited by a low concentration of penicillin G or carbenicillin in a similar manner (27), whereas the intact cells are unsusceptible to penicillin G and are relatively susceptible to carbenicillin (22).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous paper (27) it was reported that the membrane fraction derived from P. aeruginosa KM 338 catalyzes peptidoglycan synthesis, including the cross-linking reaction. This transpeptidase is inhibited by a low concentration of penicillin G or carbenicillin in a similar manner (27), whereas the intact cells are unsusceptible to penicillin G and are relatively susceptible to carbenicillin (22).…”
mentioning
confidence: 99%
“…,B-Lactamase activities were estimated by a modification of the bioassay method of Humphrey et al (13) on May 11, 2018 by guest http://aac.asm.org/ Downloaded from G was irreversibly bound to the membrane fraction which catalyzes peptidoglycan synthesis as previously described (27) (Fig. 1) (Fig.…”
mentioning
confidence: 99%
See 3 more Smart Citations